Building a carnivorous trap - Moulton, DE; Goriely, A (American Association for the Advancement of Science, 2020)
Variation, according to evolutionary biologist Stephen Jay Gould, is “nature's only irreducible essence” (1). The variation and diversity of shapes in nature is a central focus of both evolutionary and developmental biologists. Unified under the unlikely roof of “evolutionary developmental biology,” the ultimate goal of these scientists is to understand how variation arises both through natural selection (on geological time scales) and during development (on embryological time scales). On page 91 of this issue, Whitewoods et al. (2) present a fascinating example of evolutionary developmental biology in a carnivorous plant.